Perlindungan Hukum terhadap Korban yang Terjebak dalam Pinjaman Online - Shinta Dhea Salma (Syntax Literate, 2023)
The existence of technology has made it easier for people to do their activities, even now it is part of their basic needs. Another convenience offered is borrowing funds. For people who are in need of funds both in meeting their needs, business capital, and in urgent situations, they will take advantage of the existence of online loan applications. The conditions are very easy as well as the disbursement process. This is what makes people tempted to use the application. However, it does not guarantee legal protection because of the absence of legal instruments in an agreement made by both parties. In this study used a qualitative descriptive method. The aim is to understand that there is legal protection for consumers, especially those who use online loans. The result is that there are laws and regulations governing online loans. There is also listed regarding consumer protection. The government took firm steps in collaboration with OJK and Kominfo in order to eradicate illegal fintech crimes. This is in order to protect the community and manage the community regarding financial education.